1995
DOI: 10.1007/bf02329312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and salinity on embryonic development ofParacentrotus lividus (Lmk, 1816)

Abstract: The combined effects of temperature and salinity on early development of the sea urchin Paracentrotus lividus (Link, 1816) are reported. The optimal temperature-salinity combinations for development are 18 °-20 "C and 34-35%o; there is a significant temperature-salinity interaction. The optimal conditions found in the experiments are above the mean yearly values for the sampled population's environment (North Adriatic Sea), being more similar to those of the Tyrrhenian Sea. These results suggest that embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Preparing the test solutions the final dilution factor of FSW was always maintained at 10% concentration, approximately corresponding to a final salinity of 34% that is near to the value selected by His et al (1999) for tests on fertilised eggs of P. lividus and it is well within the range of salinity ''tolerance'' (33-38%) for sea urchin embryos and larvae (Bressan et al 1995). In previous experiments it was also verified that this procedure doesn't affect the results of the tests.…”
Section: Test Solutionsmentioning
confidence: 99%
“…Preparing the test solutions the final dilution factor of FSW was always maintained at 10% concentration, approximately corresponding to a final salinity of 34% that is near to the value selected by His et al (1999) for tests on fertilised eggs of P. lividus and it is well within the range of salinity ''tolerance'' (33-38%) for sea urchin embryos and larvae (Bressan et al 1995). In previous experiments it was also verified that this procedure doesn't affect the results of the tests.…”
Section: Test Solutionsmentioning
confidence: 99%
“…Experimental concentrations were chosen on the basis of preliminary trials and on literature data (Foster et al 1998;Hartgers et al 1999;His and Seaman 1993;Key and Fulton 1993;Mansueto et al 1993;Whiting et al 1996). In the preparation of test solutions the final dilution factor of FSW was always maintained at 10%, approximately corresponding to a final salinity of 34% that is near to the value selected by His et al (1999) for their tests on fertilized eggs of P. lividus and it is well within the range of salinity ''tolerance'' (33-38%) for sea urchin embryos and larvae (Bressan et al 1995). In previous experiments it was also verified that this procedure did not affect the results of the tests.…”
Section: Test Solutionsmentioning
confidence: 99%
“…Some studies concluded that temperature is one of the most limiting factors among the abiotic parameters that have influence on earliest stages of development such as fertilised eggs, zygotes and cleavage (Andronikov, 1975;Bressan et al, 1995;Swewell and Young, 1999;Sarifudin et al, 2016). Fujisawa and Shigei (1990) reported that temperature dependence is not universal but rather species specific, especially in early larval development stages.…”
Section: Discussionmentioning
confidence: 99%